AN EXPLORATION OF LAW ENFORCEMENT OFFICERS’ TRAINING EXPERIENCES, TRAINING NEEDS, AND INTERACTIONS RELATED TO AUTISM SPECTRUM DISORDER - Railey, Kirsten Scheil (2019)
Although research confirms the effectiveness of training to improve law enforcement officers’ awareness and knowledge of people with intellectual disability, learning disabilities, and mental health disorders (Bailey, Barr, & Bunting, 2001; McAllister, Bailey, & Barr, 2002; Scantlebury et al., 2017; Wood & Watson, 2017), research related to the efficacy of autism-specific law enforcement training is limited. In order to provide up-to-date information regarding training for LEOs related to autism spectrum disorder (ASD), a systematic review of the literature was conducted for the first study. Adhering to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses for Protocols 2015 (PRISMA), a search of 13 professional databases and 28 journals was conducted using search terms related to both ASD and law enforcement training. Two research team members compared decisions for study inclusion at two points, including upon initial screening and final inclusion. From 724 articles identified during the initial search, only two articles met inclusion criteria, which suggests that limited research exists that explores ASD and law enforcement training. Included studies were summarized in terms of participants as well as training format, content, and outcomes. Limitations of the current literature, directions for future research and current implications for practice are discussed. When developing trainings, it is important to consider the input of multiple stakeholders. Thus, in the second paper, qualitative data was collected through semi-structured interviews with LEOs, adults with ASD, and caregivers. Given the importance of including the ASD community in research (Pellicano, Dinsmore, & Charman, 2014), input from individuals with ASD and caregivers was obtained to complement information solely from LEOs. The goals for study two centered around (a) characterizing LEOs’ knowledge of ASD, (b) understanding LEOs’ previous interactions with individuals with ASD, and (c) identifying training needs to best prepare LEOs for interactions with individuals with ASD. In addition, members of the ASD community, including adults with ASD and caregivers, shared perspectives regarding real and hypothetical interactions with LEOs as well as suggestions regarding LEOs’ ASD-specific training needs. Researchers utilized a grounded theory approach to analyze data from 17 participants, including six LEOs, six adults with ASD, and five caregivers. All semi-structured interviews were audio recorded, transcribed, thematically coded, and summarized by researchers according to grounded theory. Common themes among participants included the (a) potential for misinterpretations of behavior of individuals with ASD, (b) helpfulness of a universal identification system/symbol for ASD, (c) need for interactive, mandatory training unique to LEOs’ needs and roles, and (d) importance of building community connections between LEOs and individuals with ASD. Together, these two studies add significant information to the current understanding of interactions between LEOs and the ASD community as well as autism-specific training for LEOs. Study one provides up-to-date information regarding evidence-based interventions for LEOs related specifically to ASD. Further, the second study provides an in-depth understanding of the interactions between LEOs and the ASD community as reported by multiple stakeholders. Across both studies, information regarding ASD-specific training, including LEOs’ prior experiences and participants’ training recommendations, can be utilized to inform the development and implementation of ASD-specific training currently being created and utilized in communities nationwide